(untitled) (Nonconventional Technologies Review, 2019)
The key factor to reducing and controlling of CO2 from environment, which is the major contributor to global warming, is the use of alternative energy systems that can be used today and may be used in the future as green energy sources. Renewable resources currently account for about 9%-10% of energy consumed in the world and most of this is from hydropower and traditional biomass sources. Each of renewable energy technologies is in a different stage of development and commercialization and all have differences in current and future expected costs, resource availability and potential impact on energy supply. This paper discusses the potential for such integrated systems in response to the critical need for a cleaner energy technology. Several issues relating to renewable energies, environment and sustainable development are examined from both current and future perspectives. On the other hand, biomass is a potential energy resource that can be converted into different forms of energy or energy carrier, such as hydrogen. In this study, also non-conventional biomass sources such as rapeseed, rapeseed cake, and rapeseed meal, had been tested for hydrogen production from biomass pyrolysis process. The influence of biomass microstructure and reducing sugar content on the hydrogen production was studied through a high-energy ball-milling pre-process of the biomass source. The results indicate that the maximum production of hydrogen was obtained at 450°C independently of the biomass source. The biomass microstructure and reducing sugar content does not seem to have an effect on hydrogen production from biomass pyrolysis.